Policy Formulation, Analytical Frameworks, and Program Design. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
The first part of this paper lays out the process of program design and briefly describes some of the analytical tools--including the financial programming framework, the balance sheet approach, and the debt sustainability template--employed by Fund country teams in advising national authorities on policy formulation. The second part of paper seeks to assess how well this process works in practice.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet